Peta Dakwah Dalam Aktivitas Keberagaman (Interaksi Islam dan Budaya di Sumatera Barat) - ASRUL HARAHAP (STAI Hubbulwathan Duri, 2019)
Da'wah in Islam is an action to call, invite, invite humanity to believe and obey to Allah SWT and return to teachings that are truly in accordance with Islamic law. Da'wah is also an effort to bring other people to Islam through kaffah, carry out all His provisions, break away from all temptations that are not from God (taghut). To achieve the preaching goals of a preacher must consider the conditions and situation, therefore a preacher needs to see the preaching map which becomes a narrative picture of the data in the field. Preaching map making has the aim to know the potential of an area, understand the shortcomings and strengths of da'wah and look for the right way of preaching in accordance with regional conditions. With the Da'wah map it can improve the Da'wah strategy and facilitate the implementation of Da'wah so that the Da'wah is successful in accordance with its objectives.